Comparison of attitudes towards statistics in graduate and undergraduate health sciences' students - Pimenta, Rui (2010)
The ultimate goal of statistical education is to provide an appropriate use of statistical thinking (Schau et al., 1995). This is particularly pertinent in the context of the health sciences since these professionals need to carry out their own investigations and make decisions under uncertainty integrating the best practices of evidence based medicine. Health professionals develop, at times, anxiety towards statistics due to their fear of mathematics. However, biostatistics courses can, nowadays, be conducted without a high level of calculus. Students’ attitudes might influence their learning of statistical concepts as much as their cognitive abilities. The influence of attitudes towards statistics on the development of statistical reasoning and thinking has been studied in different ways (Carmona, 2004; Blanco, 2008). However, the attitudes towards statistics in health sciences’ students are a new kind of research particularly pertinent due to an increasing number of students in this field. The difficulties in the use of statistics by different groups of professionals, particularly by health professionals, are well documented mainly when carrying out research. Health professionals need to promote their statistical abilities in order to be able to recognize when additional knowledge and skills are required, to obtain this additional statistical understanding or, better yet, to claim the consultation of a statistician. Improvement of positive attitudes towards statistics is a critical goal in statistics education. Positive attitudes contribute to a better use of statistical knowledge and to a better understanding of the variation inherent to data, enabling better decision-making under uncertainty when dealing with statistics. In this work, we evaluate, compare and present the first study which analyses the attitudes towards statistics in Portuguese health sciences students enrolling in postgraduate or undergraduate programs.